An exploratory study of techniques in passive network telescope data analysis - Cowie, Bradley (Rhodes University, Faculty of Science, Department of Computer Science, 2013)
Careful examination of the composition and concentration of malicious traffic in transit on the channels of the Internet provides network administrators with a means of understanding and predicting damaging attacks directed towards their networks. This allows for action to be taken to mitigate the effect that these attacks have on the performance of their networks and the Internet as a whole by readying network defences and providing early warning to Internet users. One approach to malicious traffic monitoring that has garnered some success in recent times, as exhibited by the study of fast spreading Internet worms, involves analysing data obtained from network telescopes. While some research has considered using measures derived from network telescope datasets to study large scale network incidents such as Code-Red, SQLSlammer and Conficker, there is very little documented discussion on the merits and weaknesses of approaches to analyzing network telescope data. This thesis is an introductory study in network telescope analysis and aims to consider the variables associated with the data received by network telescopes and how these variables may be analysed. The core research of this thesis considers both novel and previously explored analysis techniques from the fields of security metrics, baseline analysis, statistical analysis and technical analysis as applied to analysing network telescope datasets. These techniques were evaluated as approaches to recognize unusual behaviour by observing the ability of these techniques to identify notable incidents in network telescope datasets
Keywords: Web search engines; Internet searching; World Wide Web; Malware (Computer software); Computer viruses; Computer networks -- Monitoring; Computer networks -- Security measures